2014
DOI: 10.1099/jmmcr.0.000003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical spectrum of severe leptospirosis in the UK

Abstract: Introduction:Human leptospirosis is a global zoonotic infection with a characteristic biphasic illness and protean clinical manifestations. The majority are mild flu-like infections. The severe forms cause multiorgan damage with a greater predilection to hepatorenal failure.Case presentation:We attempted to analyse the clinical presentation of severe leptospirosis and decipher the clinical spectrum within this group by reviewing a series of 15 patients with leptospirosis requiring intensive care support for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…The shorter LOS of the fatal cases in these studies may be attributed to the severity of the cases or to the late in the admission after the onset of the symptoms [54] which make the patients at higher risk for the worse outcomes (death). Our results which showed no association of the late admission with mortality may indicate the less severity of the disease in our patients and this is supported by the less prevalence of the severe pulmonary involvement in our sample similarly to another study showed low mortality rate [84] and the less frequent severe pulmonary involvement as well. Moreover, studies showed the shorter LOS in fatal cases also showed higher fatality rate than ours indicating the higher severity of the cases in these studies which may justify the faster and higher mortality rate in those studies.…”
Section: Discussionsupporting
confidence: 86%
“…The shorter LOS of the fatal cases in these studies may be attributed to the severity of the cases or to the late in the admission after the onset of the symptoms [54] which make the patients at higher risk for the worse outcomes (death). Our results which showed no association of the late admission with mortality may indicate the less severity of the disease in our patients and this is supported by the less prevalence of the severe pulmonary involvement in our sample similarly to another study showed low mortality rate [84] and the less frequent severe pulmonary involvement as well. Moreover, studies showed the shorter LOS in fatal cases also showed higher fatality rate than ours indicating the higher severity of the cases in these studies which may justify the faster and higher mortality rate in those studies.…”
Section: Discussionsupporting
confidence: 86%
“…There is no gold standard antibiotic therapy for severe leptospirosis. Therefore, third-generation cephalosporins (ceftriaxone, cefotaxime), piperacillin-tazobactam, meropenem and doxycycline have been used with good outcome as alternatives to penicillin G 50 51. In our case, the patient responded well to triple antibiotic therapy.…”
Section: Discussionmentioning
confidence: 70%
“…In our case, the patient responded well to triple antibiotic therapy. In addition, several reports indicate that steroid therapy, specifically methylprednisolone first administered bolus intravenously and then orally, is linked to a better outcome of the patient with severe leptospirosis 6 50. Supportive therapy is important to treat any possible complications in Weil’s disease, such as fluids and electrolytes restoration, haemodialysis in severe renal impairment, supportive ventilation or even mechanical ventilation if necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The biphasic pattern of disease in European TBE is observed in only two thirds of symptomatic individuals [57]. Moreover, this pattern may occur in other viral and bacterial conditions, including Dengue, Zika [59], severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) [60], leptospirosis [61], and pulmonary anthrax [62]. evidence for preferred neuronal tropism, with neuronal cells exhibiting 10,000-fold higher TBEV replication rates than epithelial cells [52].…”
Section: Initial Viraemic Phasementioning
confidence: 99%